Knowledge, attitude, and behaviors of pregnant women about COVID-19: a single-center cross-sectional study - Gökçe Turan (Perinatal Medicine Foundation, 2021)
Objective Our aim is to assess the knowledge, attitude, and behaviors of pregnant women about COVID-19. Methods This cross-sectional survey study was performed on pregnant women in their second and third trimesters between November-December 2020. The participants completed a questionnaire consisting of 5 parts. Demographic data of pregnant women, their knowledge, attitude, and risk perceptions toward COVID-19, their practices and worries about COVID-19, and what they knew about pregnancy were calculated as percentile and mean values. Results A total of 1011 participants were included in the statistical analysis. The mean age and BMI of the participants were 27.09±5.55 and 27.48±4.71 kg/m2, respectively. Mean gestational age and parity were 26.20±9.30 and 1.47±1.19, respectively. Measures taken by authorities for COVID-19 were thought to be "extremely adequate" by 21.4% of the participants and "highly adequate" by 30%. Of the participants, 47.5% trusted healthcare professionals extremely in fighting against the COVID-19 pandemic. Affection and respect for healthcare professionals during the pandemic increased in 89.1% of the participants. Of the participants, 88.5% stated that they would follow the strict quarantine requirements when necessary and 48.3% felt more vulnerable/weak as they were pregnant during the pandemic. Of the participants, 50.6% were intending to decrease their antenatal visits during the COVID-19 pandemic. Conclusion The measures taken can be applied with high awareness of COVID-19. Sufficient training, in that case, can be done through communication routes such as information and public service announcements.